Scaling standards-aligned instruction through teacher leadership: methods, supports, and challenges - Amy Cassata; Elaine Allensworth (International Journal of STEM Education, 2021)
Abstract Background The Common Core Standards for Mathematics and Next Generation Science Standards were adopted by states with the goal of preparing students with knowledge and skills needed for college, careers, and citizenry. Adopting these standards necessitated considerable changes in instructional practice. While teacher leadership is known to be important for instructional change, there is little research that articulates the processes through which that influence occurs, and how contextual factors constrain or support those processes. This paper provides a case study of efforts in the Chicago Public Schools to promote widespread instructional change around standards reform through a teacher leader model using retrospective from 2013 to 2017 interviews with 16 math and science teacher leaders serving grades 6–12, along with quantitative analysis of district-wide data showing patterns of change and professional learning. It builds off prior research to articulate a framework of how teacher leaders promote instructional change. Findings There were five patterns of teacher leader action: inspiring others, sharing with colleagues, working in collaboration, advocating for change, and providing individual support, and an interplay between teacher actions and school-level contextual factors, with some contextual factors more important than others for different types of actions. In particular, sharing and collaborative work were facilitated in schools with designated collaboration time, trusting relationships, and colleagues who were also trained and knowledgeable about the new standards. The degree of collective efficacy the teacher leaders felt seemed to be driven mostly by the presence of other knowledgeable change agents in the school. Conclusions and implications The study adds to the existing literature on teacher leadership by articulating the mechanisms through which teachers exert influence around instructional improvement of their school peers and providing examples of each. Further, the study illustrates how these mechanisms are facilitated or constrained by the larger school context. Together, the articulation of mechanisms and contexts, along with illustrative examples, provides a guide for supporting instructional change through teacher leadership in schools and districts.